Strengthening Social Protection Network in Indonesia: A Comprehensive Analysis of Coverage, Targeting, and Funding towards an Inclusive Welfare State - Krisnadi, Muhammad Faiz (Universitas Muhammadiyah Yogyakarta, 2023)
This study analyzes the challenges and potential solutions for strengthening Indonesia's social protection network towards a welfare state system. Despite recent economic growth, poverty and inequality persist, necessitating a robust social protection network. The purpose is to identify limitations in the current system and recommend ways to transition towards a welfare state. Objectives include analyzing implementation challenges, examining potential solutions, and assessing the implications of proposed recommendations. Employing a qualitative approach, data was collected through literature reviews, government reports, and policy documents using purposive sampling. Findings indicate limitations, including inadequate coverage, targeting, and funding. Recommendations for strengthening the system include expanding coverage, improving targeting mechanisms, increasing funding, and enhancing stakeholder coordination. This study comprehensively analyses the challenges and potential solutions for strengthening Indonesia's social protection network towards a welfare state. Recommendations can inform policymakers and stakeholders in developing effective policies and programs to enhance social protection and improve the lives of vulnerable populations. The study's originality lies in its holistic approach to examining the social protection system in Indonesia and proposing practical solutions for transitioning towards a welfare state.